Computational and experimental validation of antioxidant properties of synthesized bioactive ferulic acid derivatives. Issue 1 (1st January 2018) - Adeyemi, Oluyomi Stephen; Atolani, Olubunmi; Banerjee, Priyanka; Arolasafe, Gbemisola; Preissner, Robert; Etukudoh, Promise; Ibraheem, Omodele
ABSTRACT: Ferulic acid, a well-known natural phenolic compound, is considerably reported for its hydroxyl and peroxyl radical scavenging activities. However, the antioxidant capacity of ferulic acid is limited by its relatively low solubility in hydrophobic media thereby preventing its application for autoxidation of fats and oils. To this end, several research efforts are being made to maximize the therapeutic benefits of ferulic acid and these efforts included but not limited to structural modification of ferulic acid to produce its derivatives. In this study, we synthesized ester and amide derivatives of ferulic acid and evaluated them for in vitro antioxidant potential as well as molecular docking properties. Data revealed that ferulic ester and amide derivatives had excellent antioxidant capacity and demonstrated strong inhibitory potential. Analysis of molecular docking indicated ferulic ester as potent inhibitor of target proteins in breast cancer as well as in oxidative stress. Taken together, the findings support potent antioxidant properties by these ferulic derivatives. Findings may become relevant where structural modification to enhance physico-chemical properties without compromising the antioxidant and/or medicinal potential are desirable.